Analysis Of The Effective Application Of Cross Selling In Increasing Product Sales At Dwidaya Tour Summarecon Mall Serpong - Eren Rivabelle; Feronika Berutu (Politeknik Internasional Bali, 2025)
This research aims to find out how to implement an effective cross-selling strategy in increasing product sales at Dwidaya Tour Summarecon Mall Serpong, identify supporting and inhibiting factors in its implementation, and understand customer perceptions of the strategy. This research uses a qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation. Interviews were conducted with Travel Consultants, as well as several customers who have made transactions at the branch. Meanwhile, observation and documentation were conducted for approximately three months at the research location. The results showed that the cross-selling strategy has been carried out optimally by Travel Consultants, through a personal approach. However, in its implementation, there are still some obstacles, such as limited-service time and the lack of initial customer understanding of the additional products offered. Nevertheless, customers' perceptions of the implementation of cross-selling strategies show a positive response, especially when additional product offers are delivered in a way that suits their needs.